2013
DOI: 10.1017/s0007114512005004
|View full text |Cite
|
Sign up to set email alerts
|

Biofortified cassava increases β-carotene and vitamin A concentrations in the TAG-rich plasma layer of American women

Abstract: Biofortification of cassava with the provitamin A carotenoid b-carotene is a potential mechanism for alleviating vitamin A deficiency. Cassava is a staple food in the African diet, but data regarding the human bioavailability of b-carotene from this food are scarce. The objective of the present study was to evaluate provitamin A-enhanced cassava as a source of b-carotene and vitamin A for healthy adult women. The study was a randomised, cross-over trial of ten American women. The subjects consumed three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 54 publications
3
85
0
1
Order By: Relevance
“…Bioavailability Bioconversion studies have shown a 5:1 bioequivalence between betacarotene and retinol, the form of vitamin A used by the body [13].…”
Section: Nutritional Efficacymentioning
confidence: 99%
“…Bioavailability Bioconversion studies have shown a 5:1 bioequivalence between betacarotene and retinol, the form of vitamin A used by the body [13].…”
Section: Nutritional Efficacymentioning
confidence: 99%
“…Another study with biofortified cassava porridge in the USA determined a VEB of 4.2:1 when provided with added oil and a VEB of 4.5:1 when provided without added oil (LA FRANO et al, 2013). Considering a VEB of 4.5 μg β-carotene to 1 μg retinol and an intake of 600 μg retinol daily, the consumption of 180 g of dehydrated chips obtained from BRS Jari variety and hybrid 2003 14-11 is sufficient to supply the vitamin A requirement.…”
Section: Resultsmentioning
confidence: 99%
“…The bioavailability and VA equivalency of beta-carotene in biofortified cassava was assessed in two studies in US women (Table 1) [3,4]. Women received single meals containing three different portions of cassava porridge, known as gari, which is an important fermented staple food in Sub-Saharan Africa.…”
Section: Va Equivalency Of Pva-carotenoids In Biofortified Cropsmentioning
confidence: 99%
“…The cassava meals were provided in random order, separated by 2 weeks. In the first study, women received: 1) biofortified cassava porridge with 20 g fat, 2) biofortified cassava porridge with 6 g fat, and 3) non-biofortified cassava porridge with a reference dose of preformed VA [3]. In the second study, women received: 1) biofortified cassava gari, 2) non-biofortified cassava gari blended with red palm oil (containing beta-carotene), and 3) non-biofortified cassava gari with a reference dose of preformed VA [4].…”
Section: Va Equivalency Of Pva-carotenoids In Biofortified Cropsmentioning
confidence: 99%